A dose–response correlation between smoking and severity of acute pancreatitis: a propensity score-matched study - Li, Runzhuo; Tang, Wanyun; Yan, Sun; Yu, Xiaohan; Hu, Lian (Frontiers in Medicine, 2024)
Background: Acute pancreatitis, among the most prevalent gastrointestinal disorders, exhibits a continual rise in its incidence recent years. This study endeavor to explore the correlation between smoking exposure and the severity of acute pancreatitis (AP).Methods: 508 patients diagnosed as acute pancreatitis (AP) were included in our data analysis.Patients were categorized based on their smoking pack-years into four groups: light, moderate, heavy, and non-smokers. Outcomes were classified as two: "mild acute pancreatitis (MAP)" and "moderately severe acute pancreatitis (MSAP) or severe acute pancreatitis (SAP)". We conducted propensity score matching (PSM) to adjust confounding factors and multivariable logistic regression analysis to determine adjusted odds ratios and 95% confidence intervals. Additionally, a dose-dependent association analysis between smoking exposure and the incidence rate of "MSAP or SAP" was performed.Results: Smokers exhibited a higher risk of "MSAP or SAP" compared to non-smokers, both before (17.1% vs. 54.9%, p < 0.001) and after (9.4% vs. 24.7%, p < 0.001) PSM. With an area under the ROC curve of 0.708, smoking showed a moderate level of predictive ability. Furthermore, propensity score matching analysis showed that patients who smoked compared to non-smokers had significantly higher risks of "MSAP or SAP" for light smoking (OR 3.76, 95% CI 1.40-10.07, p = 0.008), moderate smoking (OR 4.94,, p < 0.001), and heavy smoking (OR 8.08, 95% CI 3.39-19.25, p < 0.001).Smoking is an independent risk factor that can raise the severity of pancreatitis.Moreover, the severity of acute pancreatitis escalates in tandem with the accumulation of pack-years of smoking.